A new species of Cantellius and a redescription of C. sextus (Hiro, 1938) (Cirripedia, Balanomorpha Pyrgomatidae) from the elephant skin coral, Pachyseris speciosa (Dana, 1846) (Scleractinia, Agariciidae) from Taiwan - Achituv, Yair; Tsang, Ling Ming; Chan, Benny Kwok Kan (Zootaxa, 2009)
Two species of Cantellius from Taiwan were identified from the elephant skin coral, Pachyseris speciosa Dana, 1846. Cantellius sextus was found on the underside of the coral plate and a new species, C. hoegi sp. nov., on the upper surface. The microdistribution indicates the different requirements of the two species. In the present study, both arthropodal and opercular plate characters of these two species were investigated using SEM techniques. Morphologically, C. hoegi is close to C. pallidus. However, the tergal scutal margins of C. pallidus are curved, whilst those of C. hoegi are straight, and its spur is narrower than that of C. pallidus. The apex of the scutum and tergum of C. hoegi forms a honeycomb-like surface, most probably the ‘imprint’ of the chitinous primordial valves. The separation of C. hoegi from C. pallidus is also supported by molecular analyses of three mitochondrial gene sequences (COI, 16S, and 12S rRNA). Cantellius hoegi differs from C. pallidus and C. sextus by >5% in all three mitochondrial genes (COI, 16S, and 12S rRNA) sequenced. The values of sequence divergence in 12S are comparable to the inter-specific divergence reported for other Cantellius and Savignium species. Interestingly, C. hoegi is not the sister group of C. pallidus, a morphologically similar species, in the present study. Further studies should focus on molecular phylogenetic analysis of Cantellius species.